Manajemen Konflik dalam Mewujudkan Good University Governance : Analisis Penanganan Konflik Kebijakan di STITNU Al Farabi Pangandaran - Isyfi Agni Nukhbatillah; Risalatun Nisa; Nurhidayat Nurhidayat; Irpan Ilmi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
Conflict is an unavoidable phenomenon in every organization, including in higher education. Effective conflict management is key in realizing good governance in public services in higher education. This case study aims to analyze conflict management that is directly related to Good University Governance in STITNU Al-Farabi Pangandaran college. The research method is a case study with a qualitative approach. Data collection techniques through direct observation to the field and interviews with several participants. The results showed that policy conflicts in public services in higher education, namely STITNU Al-Farabi Pangandaran, can occur due to a lack of communication between the various parties involved, such as college managers, students and lecturers. In the context of handling policy conflicts, universities need to have a mechanism that can accommodate all parties involved to convey complaints and problems faced. To minimize or prevent conflicts from occurring, every college must apply the 5 principles of Good Governance; Transparency, Accountability, independence, responsibility and fairness.